2021
DOI: 10.3390/jmse9111206
|View full text |Cite
|
Sign up to set email alerts
|

Underwater Spectral Imaging System Based on Liquid Crystal Tunable Filter

Abstract: In the past decade, underwater spectral imaging (USI) has shown great potential in underwater exploration for its high spectral and spatial resolution. This proposal presents a stare-type USI system combined with the liquid crystal tunable filter (LCTF) spectral splitting device. Considering the working features of LCTF and the theoretical model of USI, the core structure containing “imaging lens-LCTF-imaging sensor” is designed and developed. The system is compact, and the optical geometry is constructed mini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Later, the underwater spectral imaging system is sealed for waterproofing followed by the optical system installation and underwater pressure test analysis. To ensure the accuracy and reliability of the spectral imaging system, imaging parameters such as spectral resolution, spectral response sensitivity, and underwater detection sensitivity are tested and calibrated with a standard monochromator and spectrometer (Song et al 2021a).…”
Section: The Underwater Spectral Imaging Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…Later, the underwater spectral imaging system is sealed for waterproofing followed by the optical system installation and underwater pressure test analysis. To ensure the accuracy and reliability of the spectral imaging system, imaging parameters such as spectral resolution, spectral response sensitivity, and underwater detection sensitivity are tested and calibrated with a standard monochromator and spectrometer (Song et al 2021a).…”
Section: The Underwater Spectral Imaging Systemmentioning
confidence: 99%
“…A liquid crystal tunable filter (LCTF) can switch its central wavelength through electrical signal control without moving mechanical structure, simplify the system structure, and improve reliability, response speed, and automation. Based on a stare-type underwater spectral imager based on LCTF (Song et al, 2021a), this paper explores the influence of different water turbidity and lighting conditions on the accuracy of spectral reflectance detection methods.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, its optical system has an unrectified axial chromatic aberration, with a focal length offset of about 0.75 mm in the visible band range of 400 nm-700 nm. Based on the previous studies [17,20], Stubbs and Stubbs [24] further found that the epiretinal imaging has a large vertical axis chromatic aberration, namely blur defocused images, due to the high axial chromatic deviation of the eyeball optical system and the large aperture or off-axis pupil characteristics. Thus, they believed that squids may adjust the accommodation between the eyeball and the retina to obtain a series of chromatic blur images at the axial position on the retina, and approximately perceive various reflected spectral components of the target object through the image contrast analysis of each frame.…”
Section: Introductionmentioning
confidence: 98%
“…Moreover, these scanning devices and platforms complicate the overall mechanical structure required in imaging. In addition, there exist other spectral imaging techniques that can be implemented by setting up a tunable light source [16] or using a liquid crystal tunable filter (LCTF) [17].…”
Section: Introductionmentioning
confidence: 99%